Mother's Motivational Factors Regarding Basic Immunization Completeness for 3 Year Old Toddlers at the "W" Mimika Timika Papua Health Center - Intan Fazrin,; Siti Ifah Nurhasanah, (Journal of Health Science Community, 2024)
The immunization program is one of the main prevention measures to avoid infectious diseases. The problem in this research is the lack of complete basic immunization coverage in the Kamoro Jaya sub-district, Wania District in 2020. The aim of this research is to analyze mothers' motivation regarding complete basic immunization for toddlers. This type of research is a Cross Sectional Study on analytical correlation. The account population is all 300 mothers from various local posyandu areas and the sample size is several mothers totaling 100 respondents using a simple random sampling technique. The dependent variable is maternal motivation and the independent variable is completeness of basic immunization. Collect data used by consent forms and questionnaires. Data processing is used by editing, coding , scoring, data entry data tabulation and used by the chi square correlation test for a number of motivational results 1 1 2 . 2 20 a And and a number of complete results 23,040. The results of the study showed that of the 100 respondents at the "W" Community Health Center, the majority (83%) were not motivated, namely 83 respondents, and the majority (74%) completed immunizations for babies, namely 74 respondents. Che square test analysis obtained p-value = 0.001 < α = 0.05 ( p-value < α) which means that H 0 is rejected and H 1 is accepted . It can be concluded that there is a relationship between motivational factors and the completeness of immunization for toddlers at the Mimika "W" Health Center Timika Papua 2020. So it is recommended that health workers pay attention to the motivation of mothers of toddlers.